Functional and Structure Outcome Intravitreal Bevacizumab in Diabetic Retinopatic with Clinically Significant Macular Edema at Bali Mandara Eye Hospital - Dewi Adnya Swari; Ni Luh Diah Pantjawati (International Journal of Retina, 2020)
Introduction: The increase in diabetics has an impact incidence of diabetic retinopathy and Diabetic Macular Edema (DME). DME due to changes in the blood retina barrier (BRB), causes fluid accumulation in the macula. This study aims to evaluate the functional outcome visual acuity and structure with optical coherence tomography (OCT) intravitreal bevacizumab (IVB) injection in DME with Clinically Significant Macular Edema (CSME). Methods: This study is a retrospective descriptive study. The study was conducted in the Department of Opthalmology, Bali Mandara Eye Hospital, Denpasar. Data were obtained from the medical records of all diabetic retinopathy patients with clinically significant macular edema who treated with IVB at Bali Mandara Eye Hospital in Denpasar January - December 2018. Result: Of the 52 subjects, improvement in best corrected visual acuity (BCVA) occurred in 26 (50.0%) subjects at the first month evaluation, 21 (40.4%) subjects at the third month, and 10 (19.2%) subjects at the sixth month evaluation. OCT decreased in 44 (84.6%) subjects at the first month evaluation, 16 (30.8%) subjects at the third month, and 14 (26.9%) subjects at the sixth month evaluation. Conclusion: There are visual acuity improvement and central retinal thickness reduction at 6 months after IVB injection. These results strengthen IVB injection to be an alternative therapy in DME with CSME.